2013
DOI: 10.20429/ijsotl.2013.070223
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Elementary Educators to Teach Reading: An Exploratory Study of Preservice Teachers’ Evolving Sense of Reading Efficacy

Abstract: Darling-Hammond, L. (2012). Creating a comprehensive system for evaluating and supporting effective teaching. Stanford, CA. Stanford Center for Opportunity Policy in Education. Duncan, A. (2011). Our future, our teachers. The Obama administration's plan for teacher education reform and improvement. Washington, DC: U.S. Department of Education. Evans, E. D., & Tribble, M. (1986). Perceived teaching problems, self-efficacy and commitment to teaching among preservice teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, embedded field experiences throughout their undergraduate education coursework may have an additive effect on pre-service teachers' perceived competence in the classroom. Kent et al (2013) study examined the evolving sense of self-efficacy in pre-service teachers as they progressed through first and second-semester reading methods courses and then student-teaching experiences. The researchers found that reading instruction self-efficacy did build through each course completion and notably after student-teaching, candidates scored significantly higher on a measure of reading teacher efficacy on 9 individual scale items than cohorts in their first or second-semester methods courses.…”
Section: Educator Preparation and Practice-based Learning Opportunitiesmentioning
confidence: 99%
“…For example, embedded field experiences throughout their undergraduate education coursework may have an additive effect on pre-service teachers' perceived competence in the classroom. Kent et al (2013) study examined the evolving sense of self-efficacy in pre-service teachers as they progressed through first and second-semester reading methods courses and then student-teaching experiences. The researchers found that reading instruction self-efficacy did build through each course completion and notably after student-teaching, candidates scored significantly higher on a measure of reading teacher efficacy on 9 individual scale items than cohorts in their first or second-semester methods courses.…”
Section: Educator Preparation and Practice-based Learning Opportunitiesmentioning
confidence: 99%
“…Technology self-efficacy of users increases with the use of technology. Time, training, vicarious experiences, positive attitude, and organizational support are required to facilitate the learning and growth of the user's self-efficacy beliefs (Kent & Giles, 2017).…”
Section: Self-efficacymentioning
confidence: 99%
“…Well prepared teachers are essential for successful schooling, given the role they have in helping young children learn to read ( Duncan, 2011 ; Kent et al, 2013 ). Their preparation to teach reading is crucial, and while conceptual and pedagogical knowledge about teaching reading is necessary ( Hikida et al, 2019 ), they also transmit their own attitudes, beliefs, and experiences as readers ( Benevides and Peterson, 2010 ; Crawford and Reidel, 2022 ).…”
Section: Introductionmentioning
confidence: 99%